2015
DOI: 10.1093/mnras/stv1646
|View full text |Cite
|
Sign up to set email alerts
|

Properties of cosmological filaments extracted from Eulerian simulations

Abstract: Using a new parallel algorithm implemented within the VisIt framework, we analysed large cosmological grid simulations to study the properties of baryons in filaments. The procedure allows us to build large catalogues with up to ∼ 3 · 10 4 filaments per simulated volume and to investigate the properties of cosmic filaments for very large volumes at high resolution (up to 300 3 Mpc 3 simulated with 2048 3 cells). We determined scaling relations for the mass, volume, length and temperature of filaments and compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 75 publications
3
64
0
1
Order By: Relevance
“…Colberg et al 2005). Our recent analysis of the gas properties of the filaments in large cosmological simulations showed that up to ∼10 3 filaments can be identified in (100 Mpc) 3 at z = 0, with a decreasing powerlaw distribution of lengths from one Mpc up to several tens of Mpc (Gheller et al, 2015). Deep imaging of the region between close pairs of galaxy clusters is potentially an efficient way to search for cosmic filaments, even if in such close configurations it might be difficult to separate the emission from cluster accretion shocks and filaments shocks.…”
Section: Filaments Connecting Clustersmentioning
confidence: 92%
“…Colberg et al 2005). Our recent analysis of the gas properties of the filaments in large cosmological simulations showed that up to ∼10 3 filaments can be identified in (100 Mpc) 3 at z = 0, with a decreasing powerlaw distribution of lengths from one Mpc up to several tens of Mpc (Gheller et al, 2015). Deep imaging of the region between close pairs of galaxy clusters is potentially an efficient way to search for cosmic filaments, even if in such close configurations it might be difficult to separate the emission from cluster accretion shocks and filaments shocks.…”
Section: Filaments Connecting Clustersmentioning
confidence: 92%
“…Thus, in essence, the outcome of these processes is that gravitational collapse naturally produces a filamentary topology, which accounts for the overall topology of the cosmic web on the largest scales, revealed both by numerical simulations and observations (e.g. Klypin & Shandarin, 1983;Van de Weygaert & Bond, 2008;Klar & Mücket, 2010;Eckert et al, 2015;Gheller et al, 2015). Note that sheets and filaments of matter appear in many other Astrophysical contexts too.…”
Section: Global Cosmological Model: Some Elementsmentioning
confidence: 95%
“…There are works that are based on visual inspection (Akamatsu et al 2017), identification of regions inter-clusters (Pimbblet et al 2004;Colberg et al 2005), or on a random configuration of galaxies based on a modelled probability distribution (Tempel et al 2014a). There are even post-processing algorithms that look for iso-densities surfaces of gas in simulations (Gheller et al 2015).…”
Section: Introductionmentioning
confidence: 99%